Madurella mycetomatis is highly susceptible to ravuconazole. - Sarah Abdalla Ahmed; Wendy Kloezen; Frederick Duncanson; Ed E Zijlstra; G Sybren de Hoog; Ahmed H Fahal; Wendy W J van de Sande (Public Library of Science (PLoS), 2014)
The current treatment of eumycetoma utilizing ketoconazole is unsatisfactory because of high recurrence rates, which often leads to complications and unnecessary amputations, and its comparatively high cost in endemic areas. Hence, an effective and affordable drug is required to improve therapeutic outcome. E1224 is a potent orally available, broad-spectrum triazole currently being developed for the treatment of Chagas disease. E1224 is a prodrug that is rapidly converted to ravuconazole. Plasma levels of E1224 are low and transient, and its therapeutically active moiety, ravuconazole is therapeutically active. In the present study, the in vitro activity of ravuconazole against Madurella mycetomatis, the most common etiologic agent of eumycetoma, was evaluated and compared to that of ketoconazole and itraconazole. Ravuconazole showed excellent activity with MICs ranging between ≤ 0.002 and 0.031 µg/ml, which were significantly lower than the MICs reported for ketoconazole and itraconazole. On the basis of our findings, E1224 with its resultant active moiety, ravuconazole, could be an effective and affordable therapeutic option for the treatment of eumycetoma.